Answers

2015-06-09T20:27:50+08:00
Quadratic Equation
x = (-b ± √b^2 - 4ac) / 2a
Where a = Numerical Coefficient of First Term
          b = Numerical Coefficient of Middle Term
          c = Numerical Coefficient of Last Term
For Example: x^2 + 2x + 1
                     a=1   b=2  c=1

x = (-b ± √b^2 - 4ac) / 2a
x = (-2 ± √4-4) / 2
x = (-2 ± 0) / 2
x sub 1 = (-2 + 0) / 2                               x sub 2 = (-2 - 0) / 2
x sub 1 = -2 / 2                                       x sub 2 = -2 / 2
x sub 1 = -1
x sub 2 = -1
So, x = 1

      
0
thank you very much i wouldn't know this if it wasn't for you so thank you again